Strengthening Business in the Banking Industry In India - Opportunities and Challenges - Srivastava, Shagun (SFIMAR Research Review, 2018)
The banking industry in India has a gigantic opus of history, which covers the traditional banking practices from the time of Britishers to the domestic reforms period, nationalisation to privatisation of banks and so on. Banking in India has been through a long journey. Banking industry also achieved new heights with changing times. The use of technology has brought a revolution in the working style of the banks. Nevertheless, the fundamental aspects of banking i.e. trust and the confidence of the people in the institution remains the same. The majority of the banks are still successful in holding the contidence of the shareholders as well as other stakeholders. However, the changing dynamics of banking business brings new kind of exposure. Delivery of E-banking facilities over public networks such as internet is bringing about a fundamental shift in the financial services industry. India is poised to experience demographic dividend in 2030. This brings good opportunities tor banks to tap the new demand trom the next generation. However, the nature of open network and the evolution of electronic commerce exposes banks to significant competition from both the banking and the tin tech firms. The electronic delivery channels operate in an uncertain legal and regulatory environment. The paper aims to explore the performance of banks with respect to customer satisfaction towards E- Banking services and other areas which affect its business. The aim of the study is to highlight the areas which the banks in India need to improve on in order to promote their business in the future. The data used for the study is secondary based on the findings of various case studies on digital banking. It is based on review of literature on the performances of some banks in different aspects like consumer’s satisfaction, innovations in technology, various banking services and the problems faced therein by consumers in availing e-banking services. It also highlights the need for banks to evolve new processes and products which shall be in demand by the next generations in India. The study portrays that the quality, range and the price of these services will decide a bank’s competitive position in the industry. A comprehensive online banking strategy and a new age banking model is imperative in the increasingly competitive business environment.